Gamification approaches to enhance critical thinking skills in elementary education: A literature review (2020-2025) - Nurma Eka Safitri; Budiyono; Bambang Subali; Arif Widiyatmoko (Jurnal Penelitian Ilmu Pendidikan, 2025)
In the transformation, entering the era of society 5.0, learners are required to proficient the 6C skills, where critical thinking ability becomes one of the essential competencies that need to be developed from elementary school levels. However, research on the integration of gamification approaches to enhance critical thinking at the elementary level remains limited, so a literature review is necessary to identify trends, challenges, and future development opportunities. The purpose of this research is to explore how using gamification can enhance critical thinking abilities in elementary schools between 2020 and 2025 using the Systematic Literature Review (SLR) method. It was established through an analysis of 22 research papers that the gamification strategy significantly enhances the critical thinking abilities of primary school pupils. Additionally, gamification helps to enhance critical thinking abilities in addition to strengthens students' cognitive, affective, and social aspects by increasing motivation, creativity, and more meaningful engagement in learning.